Gender trajectories: transsexual people coming to terms with their gender identities - Pinto, N.; Moleiro, C. (Professional Psychology: Research and Practice, 2015)
If you are a professional psychologist, it is quite likely that you have already encountered a transsexual client, or will in the future. How confident are you in your ability to work successfully with this population? Research shows that therapists' knowledge of the specific challenges that transsexual clients have to face through the course of their lives may improve clinical care. The main goal of this study was to explore how transsexual people recognize, acknowledge, and come to terms with their gender identities. In-depth interviews were conducted with a diverse sample of 22 self-identified transsexual individuals (14 male-to-female and 8 female-to-male). The analysis conformed to the principles of grounded theory methodology. Results show the participants moving through 5 developmental stages: (a) Confusion and increasing sense of gender difference; (b) Finding an explanation and a label: exploring identity; (c) Deciding what to do and when: exploring options; (d) Embracing gender identity: performing a new social identity and undergoing body modifications; and (e) Identity consolidation and invisibility. Findings also highlight various internal and external conditions, action/interaction strategies, and psychosocial consequences that participants had to cope with in each stage. We also acknowledged a series of transition triggers: that is, particular events that facilitated movement from one stage to another. Implications for clinical practice are discussed.